Serbia’s competitive position in the regional tourism destination market - Teodorović, Milivoj; Popesku, Jovan (The European Journal of Applied Economics, 2017)
The paper analyzes a competitive position of Serbia as a destination in the regional tourism market. The regional market includes Serbia’s neighboring countries enhanced by Austria, Slovenia and Greece to provide a better view of the competitive landscape of the Southeast European region herein called “Extended Balkan”. The gap analysis was applied to the selected number of global secondary indices to highlight the differential effects that impact Serbia’s position in different domains and categories, which in turn, has a profound effect on Serbia’s ability to attract, delight and retain visitors. The emphasis of this theoretical paper is on the concept and methodology rather than on the selection of indices. The paper caters to both practitioners and academics by contributing to the literature on destination competitiveness through the lens of the positioning theory.